2003
DOI: 10.1207/s15326950dp3501_2
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Problem-Solving Interactions in Young and Old Married Couples

Abstract: The study explores the importance of conversational processes for understanding collaborative cognitive performance by examining the interactions of married couples that facilitate performance on 2 everyday cognitive tasks. Twenty-four adults, 6 young (M age = 29.7 years) and 6 older (M = 70.8 years) married couples, completed a vacation decision-making task and an errand-running task. Couples were asked to talk as they performed the tasks and speech acts were coded as to whether they involved high-affiliation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 53 publications
3
87
0
1
Order By: Relevance
“…In addition to providing support and encouragement, collaborative involvement provides opportunities for spousal involvement problem solving, which can lead to better outcomes in problem solving tasks. 35,36 Dealing with initial problems is a common occurrence in CPAP use, with up to two-thirds of CPAP users reporting initial problems with this treatment. These problems often require adjusting the equipment or learning strategies to get used to sleeping with the machine.…”
Section: Change In Perceived Spousal Involvement Over 3 Monthsmentioning
confidence: 99%
“…In addition to providing support and encouragement, collaborative involvement provides opportunities for spousal involvement problem solving, which can lead to better outcomes in problem solving tasks. 35,36 Dealing with initial problems is a common occurrence in CPAP use, with up to two-thirds of CPAP users reporting initial problems with this treatment. These problems often require adjusting the equipment or learning strategies to get used to sleeping with the machine.…”
Section: Change In Perceived Spousal Involvement Over 3 Monthsmentioning
confidence: 99%
“…One key moderator comprises dyadic communication, which seems to facilitate the utilization of joint knowledge and expertise [7,59] . For example, in a series of studies Dixon and Gould [60] investigated dynamic communication patterns of young and older couples using a collaborative story recall task.…”
Section: Spousal Interrelations In Cognitionmentioning
confidence: 99%
“…Hence, appraisal-related processes seem to represent an important factor in collaborative cognition. Finally, another line of research identified affective exchanges between partners when conjointly working on tasks as a relevant mechanism in determining collaborative performance outcomes [40,59] . For example, older spouses with high-affiliation exchanges (e.g.…”
Section: Spousal Interrelations In Cognitionmentioning
confidence: 99%
“…In their study, age-related performance in the Tower of London planning task (TOL; Shallice, 1982) was compared with performance in the Plan-aday task (PAD; Funke & Krüger, 1993;Kohler, Poser, & Schönle, 1995), a task which is used to investigate more contextualized planning and which is based upon classical "daily errands" tasks (e.g., Berg, Johnson, Meegan & Strough, 2003;Hayes-Roth & Hayes-Roth, 1979;Margrett & Marsiske, 2002). While there were reliable age differences in the laboratorybased TOL, which could mostly be explained by age differences in processing speed, there were no significant age differences in the PAD, which was mostly related to participants' educational level.…”
Section: Adult Age Differences In Errand Planning: the Role Of Task Fmentioning
confidence: 99%